Acute effects of musical auditory stimulation on heart rate dynamics - do Amaral, Joice Anaize Tonon; Garner, David M.; de Abreu, Luiz Carlos; Valenti, Vitor Engrácia [UNESP] (My University, 2017)
In this chapter, we will describe recent studies that have investigated the acute influence of musical auditory stimulus on autonomic heart rate control. Searches were performed on Medline, SciELO, Lilacs and Cochrane databases using cross referencing between the keywords: “auditory stimulation,” “autonomic nervous system,” “music” and “heart rate variability.” We will present classical and recent experimental studies on humans and rats that investigated the acute effects of specific music on autonomic nervous system. For example, one of the selected studies indicated that there is a strong correlation between noise intensity and vagal-sympathetic balance. Likewise, it was conveyed that musical therapy improved heart rate variability in anthracycline-treated breast cancer patients. It was hypothesized that the release of dopamine in the striatal system induced by pleasurable songs are involved in the cardiac autonomic regulation. This chapter proposes to explore how music can be used as a complementary therapy.